CORONA VIRUS DISEASE-19 PANDEMIC - THERAPEUTICS AND NOVEL DEVELOPMENT - SAPKOTA, NIRAJ KHATRI; KOIRALA, ARUN; YADAV, RAM LOCHAN; TIMILSINA, SAMEER; BHUSAL, PUJAN (Innovare Journal of Sciences, 2021)
Every individual must follow the slogan of front line worker as “we stay at work for you, you stay at home,” This means to protect the healthcare worker who are working in the frontline to save life of the corona virus disease (COVID)-19 patient of the different phases, other should stay home safe and secured; however, if we could not protect them than the matter will be serious to everyone to control the situation of this pandemic and many life can be lost. Thus, it is suggested to the young asymptmatic people to remain quarantine and isolated until the incubation period be over, it could be as long as 41 days or as short as 6 days but average time necessary is 14 days. There are no drugs or other therapeutics presently working to knock out COVID-19 pandemic. However, drugs employed in the treatment of hospitalized patient are on the basis of previous exposure of congruent strain of virus; in addition, supportive care management such as supplemental oxygen and mechanical ventilation procedure is highly being used to the critical patient. This review highlights step to step treatment plan, employed therapeutics, mechanism, efficacy, and new development of the clinical trial results if any.